Design of a final project guidance system using the codeigniter framework at University Tjut Nyak Dhien - Zakaria Yahya Nasution (FAKULTAS SAINS DAN TEKNOLOGI - UTND, 2023)
The rapid development of technology today has forced society to keep pace with the speed of technological development. This has caused many habits and lifestyles in society to change, both in business, health, and education. Many changes have occurred since technology was implemented in the world of education. One example is the application of online-based Study Plan Card administration, it does not require a lot of paper and file storage space. However, the application of appropriate technology is still rarely implemented in the process of preparing and supervising the final project. The Information Systems Study Program at Tjut Nyak Dhien University is one of the study programs in North Sumatra. It is currently developing and trying to apply technology in its learning activities. However, in carrying out student final assignment guidance, the Information Systems study program at Tjut Nyak Dhien University still uses print-out reports and students have to queue and wait for the lecturer to correct and guide the reports that have been made. This is a problem for students and lecturers such as a waste of money and time. For this reason, it is hoped that the Tjut Nyak Dhien University Information Systems Study Program can develop a web-based system that is used for carrying out online student final assignment guidance to minimize costs and time during tutoring.